Kepatuhan Wajib Pajak UMKM Setelah Kenaikan Tarif PPn Di Desa Pematang Serai Kecamatan Tanjung Pura Kabupaten Langkat - Yunita Sari Rioni; Wan Fachruddin; Yurika Aulia (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
In facing this situation, the important role of MSMEs in supporting Indonesia's economic growth remains relevant. Even though they have great potential to contribute to the country's economy, there are still many MSMEs that have not registered as tax collectors, so tax revenues in Indonesia have not reached their maximum potential. Apart from that, the phenomenon of tax non-compliance from MSMEs may increase with the existence of regulations governing increases in VAT rates. This research aims to examine the extent to which MSMEs will comply with tax obligations after the VAT rate increase, using qualitative methods with a content analysis approach. The data used in this research includes information about MSMEs obtained from the website of the Ministry of Cooperatives and Small and Medium Enterprises, as well as data regarding the level of tax compliance of MSMEs obtained from the website of the Directorate General of Taxes.